The Influence of the Role of Parents on the Learning Achievement of Students of SDN Margorejo III Surabaya - Venasya Permata Zamrud (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2024)
This study aims to examine the influence of parental roles on students' academic achievement and identify specific roles that contribute to academic success. Using a non-experimental quantitative approach with a survey method, this study ensures the validity of the data through normality tests (Shapiro-Wilk) and homogeneity tests (Bartlett). A simple linear regression analysis was used to measure the influence of variable X (parental role) on variable Y (student academic achievement). The results showed a correlation between parental roles and academic achievement, although the effect was not statistically significant. These findings are expected to provide more in-depth insights into the factors that affect students' academic success and serve as a basis for further research.